2019
DOI: 10.7150/jca.35180
|View full text |Cite
|
Sign up to set email alerts
|

RBP7 is a clinically prognostic biomarker and linked to tumor invasion and EMT in colon cancer

Abstract: RBP7 is a member of the cellular retinol-binding protein (CRBP) family and previous data suggested a link between CRBPs and the malignant transformation of colon cancer cells. Here, we investigated the potential of RBP7 as a predictive biomarker for patients with colon cancer and determined its functional relevance for tumor progression. We analyzed RBP7 protein and mRNA expression in independent tissue collections of colon cancers with recorded follow-up data, including data from TCGA. We used gene set enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Researchers have demonstrated that MMP9 is significantly associated with poor survival of cancer patients by way of promoting the invasiveness of cancer cells [ 15 ], and high expression of MMP9 has been observed in bladder cancer patients with poor prognosis and rapid tumor progression [ 16 ]. According to Elmasry et al, overexpression of RBP7 was an independent biomarker of poor cancer-specific survival in colon cancer [ 17 ], although no studies of RBP7 in MIBC have been reported. ADIPOQ is relevant in obesity and may potentially lead to metabolic syndrome [ 18 ], thus possibly worsening the prognosis of MIBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that MMP9 is significantly associated with poor survival of cancer patients by way of promoting the invasiveness of cancer cells [ 15 ], and high expression of MMP9 has been observed in bladder cancer patients with poor prognosis and rapid tumor progression [ 16 ]. According to Elmasry et al, overexpression of RBP7 was an independent biomarker of poor cancer-specific survival in colon cancer [ 17 ], although no studies of RBP7 in MIBC have been reported. ADIPOQ is relevant in obesity and may potentially lead to metabolic syndrome [ 18 ], thus possibly worsening the prognosis of MIBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gene microarrays and RNA-sequencing have identified several prognostic biomarkers for human cancers in recent years. For instance, cytokines, 16 heat shock protein beta 3, 17 cyclin D1, 18 clusterin 19 and RBP7 20 are established prognostic markers for CRC. In addition, non-coding RNAs such as microRNAs, 21,22 long non-coding RNAs 23,24 and circRNAs 25 are increasingly reported to be associated with the survival of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…score of tumor purity for tumor tissues. Subsequent reports applied this estimation method to breast [17] and rectal cancers [18] and demonstrated the effectiveness of this algorithm. In this study, for the first time, we used TCGA data of patients with PRAD to identify a set of tumor microenvironment-related genes, which are predictive of poor prognosis in these patients.…”
Section: Introductionmentioning
confidence: 99%